Transnationalism and agency in East Malaysia: Filipina migrants in the nightlife industries - Hilsdon, Anne-Marie (Australian Anthropological Society, 2007)
East Malaysia's vibrant nightlife is a lucrative industry employing many Filipina migrants. The paper addresses the impact on Filipinas of discursive regimes of work, the state and family. These are derived from national discourses of ethnicity, class and nation intertwined with dominant discourses of womanhood in both Malaysia and the Philippines. The paper argues that in transnational space disciplinary regimes are heavily constraining, but resistance and negotiation are possible. The paper follows a feminist poststructuralist approach, which finds that disciplinary forces, rather than being coercive, are subtly inculcated in the migrant subject. Embodiment is never absolute and everyday actions of women initiate instability in the category ‘Woman’. This offers the opportunity for agency. Ethnographic methods are used to explore the tensions and constraints of the Filipinas' everyday experience of migration. In the setting of a largely non-Muslim East Malaysia, ethnic identity seems differently constructed than in a predominantly Muslim Peninsula Malaysia. Through friendship and marriage with Malaysians, and integration into local communities, Filipinas are able to resist and negotiate their migrant status. The actions of Filipinas and their local Malaysian partners contest conservative notions of ethnicity, gender, class and nation in both the Philippines and Malaysia. This offers a potential for agency for Filipinas, the possibility for which could also extend to the largely non-Muslim local Malaysians with whom they share their lives.